Dosimetric characterization of the [Formula: see text] high‐dose‐rate [Formula: see text] brachytherapy source using the AAPM and ESTRO formalism - Thanh, Minh‐Tri Ho (J Appl Clin Med Phys, 2015)
The Source Production & Equipment Co. (SPEC) model [Formula: see text] is a new [Formula: see text] brachytherapy source model intended for use as a temporary high‐dose‐rate (HDR) brachytherapy source for the Nucletron microSelectron Classic afterloading system. The purpose of this study is to characterize this HDR source for clinical application by obtaining a complete set of Monte Carlo calculated dosimetric parameters for the M‐15, as recommended by AAPM and ESTRO, for isotopes with average energies greater than 50 keV. This was accomplished by using the MCNP6 Monte Carlo code to simulate the resulting source dosimetry at various points within a pseudoinfinite water phantom. These dosimetric values next were converted into the AAPM and ESTRO dosimetry parameters and the respective statistical uncertainty in each parameter also calculated and presented. The [Formula: see text] source was modeled in an MCNP6 Monte Carlo environment using the physical source specifications provided by the manufacturer. [Formula: see text] photons were uniformly generated inside the iridium core of the model [Formula: see text] with photon and secondary electron transport replicated using photoatomic cross‐sectional tables supplied with MCNP6. Simulations were performed for both water and air/vacuum computer models with a total of [Formula: see text] sources photon history for each simulation and the in‐air photon spectrum filtered to remove low‐energy photons below [Formula: see text]. Dosimetric data, including [Formula: see text] , and [Formula: see text] , and their statistical uncertainty were calculated from the output of an MCNP model consisting of an [Formula: see text] source placed at the center of a spherical water phantom of 100 cm diameter. The air kerma strength in free space, [Formula: see text] , and dose rate constant, Λ, also was computed from a MCNP model with [Formula: see text] [Formula: see text] source, was centered at the origin of an evacuated phantom in which a critical volume containing air at STP was added 100 cm from the source center. The reference dose rate, [Formula: see text] , is found to be [Formula: see text]. The air kerma strength, [Formula: see text] , is reported to be [Formula: see text] , and the dose rate constant, Λ, is calculated to be [Formula: see text]. The normalized dose rate, radial dose function, and anisotropy function with their uncertainties were computed and are represented in both tabular and graphical format in the report. A dosimetric study was performed of the new [Formula: see text] [Formula: see text] HDR brachytherapy source using the MCNP6 radiation transport code. Dosimetric parameters, including the dose‐rate constant, radial dose function, and anisotropy function, were calculated in accordance with the updated AAPM and ESTRO dosimetric parameters for brachytherapy sources of average energy greater than 50 keV. These data therefore may be applied toward the development of a treatment planning program and for clinical use of the source. PACS numbers: 87.56.bg, 87.53.Jw